1988
DOI: 10.1177/088636878802000103
|View full text |Cite
|
Sign up to set email alerts
|

Reward Policies That Support Entrepreneurship

Abstract: Becnrrse the sirccess of eritreprerierrrs~ziys deperids ori irirzovntive, crenfive eiiiployees z o h nre zoillirrg f o nccept risk, sircli orgn,iizntioris riirrsf develop coiiiperisnfioii policies t h t rezonrd srrch Gehnviors. Reward Policies That SupporfEn h e p re n e urs h ip '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
2
17
0
6
Order By: Relevance
“…This suggested that respondents regarded that every factor does play an important role in innovation success. The finding is consistent with prior researchers (Byers et al, 2011;Saleh & Wang, 1993;Panne et al, 2003;Jacobides, 2007;Balkin & Logan, 1988;Haas & Hansen, 2005;Wong, 2005;Cooper & Kleinschmidt, 2007). According to Byers et al (2011), a positive organization culture such as trust and cooperation, knowledge sharing, openness to new ideas and tolerance to failure serves as a set of powerful stimulant tools for positive innovative behavior and innovation success in organization.…”
Section: Addressing Ro1: Important Level Of Success Factors For Innovsupporting
confidence: 82%
See 1 more Smart Citation
“…This suggested that respondents regarded that every factor does play an important role in innovation success. The finding is consistent with prior researchers (Byers et al, 2011;Saleh & Wang, 1993;Panne et al, 2003;Jacobides, 2007;Balkin & Logan, 1988;Haas & Hansen, 2005;Wong, 2005;Cooper & Kleinschmidt, 2007). According to Byers et al (2011), a positive organization culture such as trust and cooperation, knowledge sharing, openness to new ideas and tolerance to failure serves as a set of powerful stimulant tools for positive innovative behavior and innovation success in organization.…”
Section: Addressing Ro1: Important Level Of Success Factors For Innovsupporting
confidence: 82%
“…Whereas, in accordance with Saleh and Wang (1993), Panne et al (2003), and Jacobides (2007), organization structure that allows sufficient flexibility, promote organization's communication and integration, underline task allocation and encourage cross functional teams' cooperation are also important attributes for innovation management success. In addition, leadership which included knowledge of leader, characteristics of leader, subordinates empowerment and reward system are also perceived as important for innovation management which is in line with finding by Balkin and Logan (1988) …”
Section: Addressing Ro1: Important Level Of Success Factors For Innovsupporting
confidence: 50%
“…La remuneración en las firmas emprendedoras es más igualitaria, ya que la estructura jerárquica es bastante plana (Balkin y Logan, 1988;Graham, Murray y Amuso, 2002) y se entiende más como una compensación por el riesgo que corre el empleado en este tipo de empresas (Cardon y Stevens, 2004;Dal Zotto y Gustafsson, 2008).…”
Section: Política De Remuneraciónunclassified
“…Los incrementos salariales de las pequeñas empresas también difieren de las grandes, ya que en estas últimas suelen estar automatizados anualmente (Balkin y Logan, 1988). En las pequeñas empresas el salario es un coste fijo, si bien estas empresas no tienen certeza en las ventas o los beneficios que van a tener, por lo que optan por conceder bonificaciones (Cardon y Stevens, 2004).…”
Section: Política De Remuneraciónunclassified
See 1 more Smart Citation